Evidence in Civil Law - Sweden - Bylander, Eric (Law & Society, 2015)
This publication is based on the Swedish report to the project Dimensions of Evidence in Civil Procedure. The major objective of the project has been to explore whether there exists a common core of European Law of Evidence, and if it does, to describe its content and its most important points of discord among the national legal systems. By providing a clear picture of common core principles, the project can serve as a starting point for further harmonisation or unification processes in this field. A basic assumption of the project is that there can be no trust without a clear picture what courts do in matters of evidence, and how they discover the facts. This publication presents the relevant aspects of the Swedish legal system. The Swedish system for adjunction seldom takes its ground in firmly defined principles, but principles appear in decisions ad hoc. The Swedish application of the principle of free production of evidence and the principle of free assessment of evidence are far-reaching.